Clinical evaluation of technology lipido-colloid in the management of acute wounds in China. Issue 3 (2020) - Qiuju, Dr Li; Xiaohong, Dr Li; Liang, Dr Qiao; Shihong, Dr Tong; Hongnv, Dr Zheng; Galea, Emilio
No abstract available